Influence of the perception of leadership styles on the authenticity of female entrepreneurs : the role of internal communication - Oedekoven, Frauke (2022)
The number of women in leadership positions and women starting their own businesses has noticeably grown over the course of the past decades. Despite this positive trend, an underrepresentation of female leaders is yet still detectable. This rather young development towards closing the gender gap in leadership consequently also implies an underrepresentation of female leader role models. This research investigates how the leadership styles of female entrepreneurs are shaped through previously perceived leadership styles. Further, it explores whether these perceptions influence the authenticity of their own leadership styles and how they communicate internally. Hence, next to investigating the influence of leadership perceptions, this research provides an examination of Authentic Leadership behavior of female entrepreneurs and of their internal communication structures. For this investigation, a mixed methods research approach was carried out by conducting four semi-structured interviews with female entrepreneurs from Germany and gathering supportive data from the respective employees through quantitative online surveys. Subsequently the raw data was analyzed and evaluated to answer the research question and five derived propositions. The findings indicate that the influence of previously perceived leadership styles on the leadership style of female entrepreneurs is rather low or even non-existent. While the studied women all showed Authentic Leadership traits, indicators for Two-Way Symmetrical Internal Communications systems could be found, but not reliably confirmed due to insufficient quantitative data. Aligning with previous studies, a positive relation between Authentic Leadership and Two-Way Symmetrical Communication could be identified. Further, it was found that female entrepreneurs rather follow their intuition during their initial leadership style development than specific role models.